Treatment Burden of Weekly Somatrogon vs Daily Somatropin in Children With Growth Hormone Deficiency: A Randomized Study - Maniatis, Aristides K; Carakushansky, Mauri; Galcheva, Sonya; Prakasam, Gnanagurudasan; Fox, Larry A; Dankovcikova, Adriana; Loftus, Jane; Palladino, Andrew A; de Los Angeles Resa, Maria; Turich Taylor, Carrie; Dattani, Mehul T; Lebl, Jan (Journal of the Endocrine Society, 2022)
CONTEXT: Somatrogon is a long-acting recombinant human growth hormone treatment developed as a once-weekly treatment for pediatric patients with growth hormone deficiency (GHD). OBJECTIVE: Evaluate patient and caregiver perceptions of the treatment burden associated with the once-weekly somatrogon injection regimen vs a once-daily Somatropin injection regimen. METHODS: Pediatric patients (≥3 to <18 years) with GHD receiving once-daily somatropin at enrollment were randomized 1:1 to Sequence 1 (12 weeks of once-daily Somatropin, then 12 weeks of once-weekly somatrogon) or Sequence 2 (12 weeks of once-weekly somatrogon, then 12 weeks of once-daily Somatropin). Treatment burden was assessed using validated questionnaires completed by patients and caregivers. The primary endpoint was the difference in mean overall life interference (LI) total scores after each 12-week treatment period (somatrogon vs Somatropin), as assessed by questionnaires. RESULTS: Of 87 patients randomized to Sequence 1 (n = 43) or 2 (n = 44), 85 completed the study. Once-weekly somatrogon had a significantly lower treatment burden than once-daily Somatropin, based on mean overall LI total scores after somatrogon (8.63) vs Somatropin (24.13) treatment (mean difference -15.49; 2-sided 95% CI -19.71, -11.27; P < .0001). Once-weekly somatrogon was associated with greater convenience, higher satisfaction with treatment experience, and less LI. The incidence of treatment-emergent adverse events (TEAEs) for Somatropin and somatrogon was 44.2% and 54.0%, respectively. No severe or serious AEs were reported. CONCLUSION: In pediatric patients with GHD, once-weekly somatrogon had a lower treatment burden and was associated with a more favorable treatment experience than once-daily Somatropin.
Keywords: NGENLA; Somatropin; somatrogon; growth hormone; long-acting growth hormone; growth hormone deficiency